Self-Management Pada Lansia Penderita Hipertensi Di Desa Tanak Beak Wilayah Kerja Puskesmas Narmada: Self-Management for Elderly People Suffering from Hypertension in Tanak Beak Village, Narmada Health Center Working Area - Heni, Baik Heni Rispawati; Ernawati; Supriyadi; Riskawaty, Heny Marlina (Jurnal Abdi Keperawatan dan Kedokteran, 2023)
Hypertension is also known as the "Silent Killer". Someone is said to be hypertensive if systolic blood pressure is often found ≥ 140 mmHg and diastolic pressure ≥ 90 mmHg. In this service, it aims to find out how the community in the village of Tanak Beak, Narmada sub-district, regarding self-efficacy and self-management in elderly people with hypertension in Tanak Beak Village, the work area of the Narmada Health Center, Kab, West Lombok. The low level of self-management in elderly people with hypertension who receive long-term treatment is due to lack of knowledge and boredom, so the treatment program is not successful. Elderly with hypertension who do not have good faith and lack self-care management, causing further complications. The method used in this service is to identify people who have hypertension, then check their blood pressure and provide material related to self-efficacy and self-management. In this service, 62 respondents were found to have hypertension, and after being given counseling about self-efficacy and self-management, the community understood how.